Thomas W. Arnold (2012). The Spread of Islam in the World: A History of Peaceful Preaching. New Delhi: Goodword Books. 467 pages. [ISBN: 8187570229] - Idris, Asmady (Journal of Al-Tamaddun, 2022)
Arnold’s book offers a balanced analysis and an alternative perspective for those who seek to find the truth about Islam. It has 13 chapters (including introduction and conclusion) and each chapter covers almost all regions that had interacted with Islam. The story line of the book begins with how Islam first established in Mecca and Medina, and later it spreads to all Arabian Peninsula and other corners of the earth encompassing western Asia, Africa, Spain Andalusia, central Asia, China, India, and Malay Archipelago. In the time of writing in 1896, Prof Arnold estimated that there were about 200 million of the followers of Islam. The references used in this book range from Arabic, Dutch, English, French and other sources.The main strength of this book is it reveals with an avalanche data of how Islam peacefully spread to many places in the world. Professor Arnold has laid down the very fundamental vigour of Islam which is not entirely depending on the Muslim physical empires and dynasties but it solidly rests on its ‘spiritual conquests’, that is, da’wah conveying the message of Islam that went on uninterruptedly by the Muslim missionaries.